1983
DOI: 10.1111/j.1365-2044.1983.tb13925.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐oxygenation–how long?

Abstract: Pie-oxygenation was studied in I 2 j t volunteers and 20 patients using an oxygenJow of8 litreslminute delivered from a standard anaesthetic machine via a Uagill or Bain breathing attachment. End-tidal nitrogen concentrations of PA or less were achieved within 3 minutes; the fartest times were achieved using rhe Mngill breathing system when the reservoir bag wasfilled with oxygen prior to application to the face. Gas-tight fits of face masks on patients were found to be essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
6

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(39 citation statements)
references
References 3 publications
1
32
0
6
Order By: Relevance
“…7,8 However, these preoxygenation techniques require a tightly fitting face mask, and do not account for the leaks that occur frequently in practice. [9][10][11][12] Leaks have been reported in 10 to 11.5% of subjects with no facial anomalies and normal dentition. 13,14 In real life, leaks probably occur even more frequently since we often preoxygenate patients who are edentulous, wear beards or mustaches, have a nasogastric tube in place, or cooperate poorly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 However, these preoxygenation techniques require a tightly fitting face mask, and do not account for the leaks that occur frequently in practice. [9][10][11][12] Leaks have been reported in 10 to 11.5% of subjects with no facial anomalies and normal dentition. 13,14 In real life, leaks probably occur even more frequently since we often preoxygenate patients who are edentulous, wear beards or mustaches, have a nasogastric tube in place, or cooperate poorly.…”
Section: Discussionmentioning
confidence: 99%
“…10 Berthoud et al realized that allowing even one breath contaminated with air increased end-tidal nitrogen concentration markedly. 9 Drummond et al…”
mentioning
confidence: 99%
“…For many years, the traditional tidal volume breathing (TVB) for three to five minutes has been commonly practiced. 4,5 The period required for preoxygenation has been shortened by using deep breathing (DB), as advocated by Gold et al, 6 who used four deep breaths in 30 sec and by Baraka et al 7 who recommended eight deep breaths within 60 sec. More recently, it has been found that extending the duration of DB to 1.5 or two minutes with high fresh gas flow (FGF) further improves the efficacy of preoxygenation.…”
Section: Résultats : La Respiration En Volume Courant Avec Une Expiramentioning
confidence: 99%
“…por cerca de 2 a 5 minutos (Berthoud et al, 1983;McGowan, Skinner, 1995;Gerardi et al, 1996). Desta maneira, o doente estaria apto a tolerar alguns minutos de apneia sem queda da saturação de O 2.…”
Section: Figura 5 Frequência Das Causas Sriunclassified
“…A pré-oxigenação a 100%, mantendo a ventilação espontânea, sem a utilização da VPP, visa a reduzir os riscos associados à hiperinsuflação gástrica, como regurgitação e aspiração do conteúdo gástrico (Berthoud et al,, 1983 A compressão cricoide, também chamada de manobra de Sellick, consiste na aplicação de uma pressão contínua na cartilagem cricoide (Sellick,1961) e foi descrita, inicialmente, durante os procedimentos de anestesia. Na SRI é fundamental e amplamente recomendada, prevenindo a regurgitação passiva do conteúdo gástrico para a faringe e a insuflação gástrica durante a ventilação com pressão positiva e para prevenir a aspiração pulmonar durante o procedimento de IT (Walls, 2004;Walls et al, 2007;Ellis et al, 2007).…”
Section: Figura 5 Frequência Das Causas Sriunclassified